The colors of mice : a model genetic network - Lamoreux, M. Lynn. (Chichester, West Sussex : Wiley-Blackwell, 2010)
Serving the needs of pigment cell biologists, cellular physiologists, developmental geneticists, researchers interested in melanoma and more, this new book brings to market a blend of new technologies and new insights in the fields of both pigmentation and mouse geneticists. It will include some comparative information on other organisms as well. The book is hailed for being written by some of the premier scientists in the field. These authors aim to present the molecular /cellular work in the context of phenotype and the interacting functions of genes that direct the development and function of one biological system. Interactions over details that can be found on the web are stressed. Overall the pigmentary systems provides a model for the study of all systems because it is a particularly well developed model --Provided by publisher.
Machine generated contents note: Part one-The Pigmentary System.1. Introduction to the System.2.Introduction to the Mutants/List of Loci.Part Two-Mutant Mice.3.White spotting.4. Melanosomal/Melanogenic.5. Pigment Type Switching.6. Melanosome Transport.7. Melanosome Transport.Part Three-Current Approaches.8. New Technologies.9. Other Species, Sequencing, Comparative studies.10.Appendices.
Includes bibliographical references (p. [243]-285) and index.
Keywords: Gene Regulatory Networks -- physiology; Models, Animal; Models, Genetic; Pigmentation -- genetics; Pigments, Biological -- genetics; Mice -- Genetics